The Role of Artificial Intelligence in Financial Risk Management in Fintech Companies - Siska Yuli Anita; Irsyad Kamal; Loso Judijanto; Johnny Chandra; Rizal Perlambang C NAWP (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2025)
This study aims to examine the impact of the application of Artificial Intelligence (AI) in financial risk management in FinTech companies. With the increasing reliance on technology, AI has great potential in managing various types of risks, such as credit, market and liquidity risks. This study uses a quai-experimental approach by comparing two groups of companies, namely companies that use that do not use AI. The data collected included the level of non-performing (NPLs), market value fluctuations, and liquidity stability, which were analyzed using t-test and ANOVA to identify significant differences between the two groups. The results showed that companies that implemented AI experienced a significant decrease in bad debt rates, more manageable market values fluctuations, and improved liquidity stability. However, the main challenges faced in implementing AI include limited quality data technological comnpetency, and regulatory compliance. Overall, this study reveals that the application of AI can improve the effetiveness of financial risk management in FinTech firms, but requires investment in employee training, technological infrastructure development, and attentionto regulatory aspects to maximize the benefits.